2004
DOI: 10.2214/ajr.182.3.1820587
|View full text |Cite
|
Sign up to set email alerts
|

Value of Fat Suppression in the MRI Evaluation of Suspected Arrhythmogenic Right Ventricular Dysplasia

Abstract: The use of fat-suppressed in addition to non-fat-suppressed conventional T1-weighted spin-echo imaging increased interobserver agreement and confidence in diagnosis and evaluation of intramyocardial fatty infiltration in patients who were suspected to have ARVD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 12 publications
1
9
0
Order By: Relevance
“…That study was multicenter and used non-breath hold conventional spin imaging; a method not currently used at most sites owing to low image quality with resulting frequent motion artifacts. Our findings are similar to the single-center results reported by Abbara et al (14), who used conventional spin-echo images with fat suppression and demonstrated good agreement for intramyocardial fat detection. However, the utility of fat-suppression was not separately assessed in our study.…”
Section: Discussionsupporting
confidence: 91%
“…That study was multicenter and used non-breath hold conventional spin imaging; a method not currently used at most sites owing to low image quality with resulting frequent motion artifacts. Our findings are similar to the single-center results reported by Abbara et al (14), who used conventional spin-echo images with fat suppression and demonstrated good agreement for intramyocardial fat detection. However, the utility of fat-suppression was not separately assessed in our study.…”
Section: Discussionsupporting
confidence: 91%
“…Firstly, it is shown how radiofrequency (rf) preparation pulses can be added to existing pulse sequences to alter their contrast behaviour: An inversion pulse added to a black-blood FSE/TSE pulse sequence enhances T1 and T2 weighted contrast for imaging of myocardial oedema [10]. A fat suppression pulse added to an existing pulse sequence selectively suppresses the MR signal contribution from lipid based tissues [11], thus improving the delineation of non-lipid based structures. More complex preparation pulses may also be added to the cine gradient echo pulse sequence to apply a line or grid pattern to achieve myocardial tissue tagging that allows visualisation of intra-myocardial motion [12,13].…”
Section: Reviewmentioning
confidence: 99%
“…One relatively commonly employed pulse sequence for T2-weighted CMR imaging is short-inversion-time inversionrecovery (STIR) imaging, which imparts T2 contrast based on a preparation consisting of several short inversion pulses prior to image read-out and demonstrates minimal fat signal (212). Following pre-contrast T1-and T2-weighted image acquisition, images with and without fat suppression pulses should be obtained so that regions of interest that may contain fat may be identified and considered (213,214).…”
Section: Cmr Protocol For Cardiac Tumorsmentioning
confidence: 99%